2021
DOI: 10.2139/ssrn.3865465
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Inattention in the (Baseball) Field

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Relatedly, a recent study of baseball umpires showed that umpires tire of making decisions about strikes and balls over the course of a game, depleting their budget of attention and leading to errors as the game progresses. 43 These dynamics effect elites and members of the mass public when they are trying to act under pressure. When offering advice, experts seldom offer only one path forward.…”
Section: An Oversupply Of Advicementioning
confidence: 99%
“…Relatedly, a recent study of baseball umpires showed that umpires tire of making decisions about strikes and balls over the course of a game, depleting their budget of attention and leading to errors as the game progresses. 43 These dynamics effect elites and members of the mass public when they are trying to act under pressure. When offering advice, experts seldom offer only one path forward.…”
Section: An Oversupply Of Advicementioning
confidence: 99%
“…Specifically, I link the ENEM records to a census of all Brazilian college students and an employee-employer matched dataset that covers the universe of formal-sector workers in Brazil. Linder et al, 2014;Kim et al, 2018); financial analysts make less accurate forecasts (Hirshleifer et al, 2019); and umpires make more incorrect calls in baseball games (Archsmith et al, 2021). 4 For example, in the US, 65% of adults drink coffee daily (Lampkin, 2012), and about 20% of college students report using nootropics without a prescription to enhance focus and cognition (Benson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%